Towards an Effective Legal Identity Based on the Provisions of Islamic Jurisprudence in Civil Transactions - Mahasneh, Nisreen (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2024)
The present study addresses the legal identity of Arabs and Muslims, particularly in the area of civil transactions (an area that may be viewed as worldly or mundane rather than subject to Islamic law). Such an identity can only be established via the provisions of Islamic jurisprudence, which has laid down a number of pillars, principles, and theories in the realm of civil transactions. Scholars working in the renewal of Islamic legal thought have endeavored to highlight the provisions of Islamic jurisprudence and link them to contemporary applications and legal developments, thus enabling modern Islamic jurisprudence to create legitimate alternatives to modern legal formulas and models based on general theories and universal principles from which controls for new transactions may be deduced. The study shows that Islamic jurisprudence is a divinely inspired legal system with respect to general foundations and principles, and that it is rich with provisions governing worship, transactions, and legislation. Nevertheless, it has not emerged on the national or international scene as an influential legal system. Some Arab legislation has been influenced by, and drawn upon, Islamic jurisprudence; however, this influence has been piecemeal. Hence, unlike the Anglo-Saxon and Latin legal systems, Islamic jurisprudence has failed to achieve a legal identity or emerge as a legal school in international models concerned with civil transactions. Therefore, work must be done to propagate the culture of Islamic jurisprudence globally, and to overcome the political considerations that have prevented previous initiatives from achieving this aim.